Ambulatory Otologic Surgery, a 5-year audit of a tertiary care landscape: An Audit - Abdul Basit Shah Vardag; Farzeen Omer; Malik Ali Hasham Awan; Mohammad Sohail Awan (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the frequency and characteristics of readmissions following ambulatory daycare otological surgeries. Method: The retrospective, cross-sectional study was conducted in December 2024 at the Department of Otolaryngology and Head and Neck Surgery, Aga Khan University Hospital, Karachi, and comprised data of patients who underwent therapeutic ambulatory otological procedures, such as cochlear implantation, tympanoplasty, myringoplasty, mastoidectomy and stapedectomy/stapedotomy, between September 1, 2019, and October 1, 2024. Data was analysed using SPSS 23. Results: Of the 825 patients with mean age 30.43±14.45 years, 433(52.5%) were male and 392(47.5%) were female. The most common procedure was tympanoplasty 605(73.3%), followed by cochlear implantation 104(12.6%), stapedectomies 67(8.1%) and mastoidectomy 49(6.1%). Among the 63(7.6%) unplanned cases, 42(66.67%) were classified as minor complications. The most common reasons for unplanned readmissions were wound care issues 34(53.9%), followed by local swelling/pain 7(11.1%) and bleeding 10(15.8%). Readmissions occurred within 10 days post-surgery in 62(98.4%) cases, with only 1(1.6%) patient experiencing a delayed complication in the shape of facial nerve paralysis. Conclusion: Ambulatory otological surgeries were found to be safe and feasible with a low complication rate. Key Words: Ambulatory surgery, Ear surgical procedures, Patient readmission, Tympanoplasty, Cochlear implantation, Wound infection, Postoperative complications.